Fusion tags for protein solubility, purification and immunogenicity in Escherichia coli: the novel Fh8 system - Costa, Sofia; Almeida, André; Castro, António; Domingues, Lucília (Frontiers in Microbiology, 2014)
Proteins are now widely produced in diverse microbial cell factories. The Escherichia coli is still the dominant host for recombinant protein production but, as a bacterial cell, it also has its issues: the aggregation of foreign proteins into insoluble inclusion bodies is perhaps the main limiting factor of the E. coli expression system. Conversely, E. coli benefits of cost, ease of use and scale make it essential to design new approaches directed for improved recombinant protein production in this host cell. With the aid of genetic and protein engineering novel tailored-made strategies can be designed to suit user or process requirements. Gene fusion technology has been widely used for the improvement of soluble protein production and/or purification in E. coli, and for increasing peptide’s immunogenicity as well. New fusion partners are constantly emerging and complementing the traditional solutions, as for instance, the Fh8 fusion tag that has been recently studied and ranked among the best solubility enhancer partners. In this review, we provide an overview of current strategies to improve recombinant protein production in E. coli, including the key factors for successful protein production, highlighting soluble protein production, and a comprehensive summary of the latest available and traditionally-used gene fusion technologies. A special emphasis is given to the recently discovered Fh8 fusion system that can be used for soluble protein production, purification and immunogenicity in E. coli. The number of existing fusion tags will probably increase in the next few years, and efforts should be taken to better understand how fusion tags act in E. coli. This knowledge will undoubtedly drive the development of new tailored-made tools for protein production in this bacterial system.